Weed Infestation and Productivity of Maize/Soybean Inter crop As Influenced by Cropping Pattern in the Southern Guinea Savanna of Nigeria - Emmanuel, Imoloame Oyamedan; Ahmed, Kafayat B. (Journal of Agricultural Sciences (Belgrade), 2018)
Field experiments were conducted during the 2015 and 2016 cropping seasons at the Teaching and Research ( T & R) Farm of the College of Agriculture, Kwara State University Malete, to determine the effect of cropping pattern on weed infestation, growth and yield of maize/soybean intercrop in the southern Guinea savanna of Nigeria. The experiments consisted of six treatments as follow : one row of maize alternating with one row of soybean (1 :1), one row of maize alternating with two rows of soybean (1:2), two rows of maize alternating with one row of soybean (2:1 ), two rows of maize alternating with two rows of soybean ( 2: 2), a sole maize (1:0) and a sole soybean (0 :1). The treatments were laid out in randomized complete block design with three replicates. Data collected were subjected to analysis of variance and means were separated by least significant difference (LSD) at 5% level of probability. Results showed that sole soybean consistently suppressed weed and resulted in higher yield of soybean. Similarly, 2 maize:1 soybean, did not only reduce weed density, it produced significantly higher yields of maize and lower yield of soybean, had the higher land equivalent ratio and economic returns followed by the sole maize.